ANALISIS UJI KESELAMATAN LISTRIK DAN KALIBRASI CENTRIFUGE - Rizka, Hidayah; Yulizham; Abdillah, Khairil; Ulina, Sri (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2022)
Health equipment is a supporting tool for medical service facilities. Room temperature is also very important in the placement of medical devices so that there are no errors in reading the equipment or damage to medical devices can occur. Calibration is an activity to determine the conventional truth of the value of the indication of measuring instruments and measuring materials by comparing them to traceable measuring standards to national and international standards for units of measure and/or international and certified reference materials. The method used in conducting electrical safety test analysis and calibration on the centrifuge is ECRI, IEC 60601-2. The results of environmental measurements at temperature and humidity meet the requirements with a measured room temperature of 23°C and room humidity of 57.1%, the results of the electrical safety test measurement are declared safe and measured. Protective earth resistance is 0.432mΩ, equipment leakage current is 0.1µA and insulation resistance is 11.1MΩ , the results of the rotational speed accuracy measurement meet the tolerance limits of each value, for setting 2000RPM, 2500RPM, 3000RPM, 3500RPM, 4000RPM there is a deviation of 14.8 with an uncertainty value of 7.0 RPM, the results of the time accuracy measurement meet the tolerance limit with a setting value of 5 minutes (300 seconds) there is a deviation of 1.6 seconds with an uncertainty value of 2.55 seconds, for a full automatic Centrifuge with type HC-16D with Serial No. 2H01018 declared fit for use because it meets the tolerance limit.